Determinants of Entrepreneurial Financial Wellbeing in Dang District of Western Nepal (The International Research Journal of Management Science, 2025)
Purpose: The purpose of this paper is to explore the determinants of entrepreneurial financial wellbeing in Dang district of western Nepal.Method(s): The causal comparative research design was adopted as the positivist research paradigm to discover objective reality. The paper adopts a survey by questionnaire method to gather data from 412 entrepreneurs through the purposive sampling under non-probability sampling technique. The data was evaluated by using descriptive and inferential statistics. Measurement modeling as well as structural equation modeling (SEM) was used and data analyzed by PLS 4.1.1.2.Finding(s): The study’s findings show that mental budgeting; materialism and self-control have a significantly influenced on financial wellbeing of entrepreneurs but financial literacy haven’t significantly influenced on financial wellbeing of entrepreneurs.Conclusion: This study shows that the entrepreneurs of Dang district are mentally prepared regarding budgeting, focused on materialism and able to self-control. Hence, there is a considerable possibility of financial wellbeing of entrepreneurs, according to the research.Implication(s): This study has significant implications to entrepreneurs, policymakers and financial institutions in Nepal.Originality: This research is original and is not published in other publications.